A moderated mediation model linking entrepreneurial leadership to green innovation: An upper echelons theory perspective. (27th December 2022) - Ali, Adnan; Jiang, Xu; Ali, Afzaal; Qadeer, Abdul
Abstract : Despite the dominant discourses on the important role of entrepreneurial leadership in firms' development, related theoretical and empirical studies are still lacking in the environmental management area. Adopting upper echelons theory, this study develops a moderated mediation model that examines how entrepreneurial leadership affects the adoption of green innovation (GI) through organizational learning culture and how environmental dynamism moderates the mediating effect. This theoretical model is tested using a sample of 248 Chinese firms. Findings support the positive impact of entrepreneurial leadership on GI and the mediating role of organizational learning culture. The moderated mediation path analysis shows that environmental dynamism moderates the indirect effect of entrepreneurial leadership on GI via organizational learning culture. Overall, this study adds to entrepreneurship and environmental management scholarship by providing novel insights into the key role of entrepreneurial leadership in embracing GI.